Learning about the Future and Dynamic Efficiency - Gershkov, Alex; Moldovanu, Benny (American Economic Review, 2009)
We study an allocation problem where a set of objects needs to be allocated to agents arriving over time. The basic model is of the private, independent values type. The dynamically efficient allocation is implementable if the distribution of agents' values is known. Whereas lack of knowledge about the distribution is inconsequential in the static case, endogenous informational externalities arise if the designer gradually learns about the distribution by observing present values. These externalities may prevent the implementation of the dynamically efficient allocation. We provide necessary and sufficient conditions for the efficient allocation to be implementable. (JEL D11, D82)